DUKUNGAN PEMERINTAH DALAM MENCEGAH PENYALAHGUNAAN NARKOBA DI KOTA SURABAYA - Nuri Pina; Oedojo Soedirham (Universitas Airlangga, 2017)
Drugs are a serious problem that need to be solved together. Based on the data from City Narcotics Agency (BNNK) the number of drug abusers in Surabaya is increased. The city of Surabaya has issued local law (Perwali) Number 65 of 2014 about policies and strategies for the area in the field of prevention, Combating Drug Abuse and Illicit Drugs (P4GN). The regulation has been in accordance with the healthy public policy. The aim of this study is to determine the government's support in preventing drug abuse. The special purpose is to determine the achievement of the target, implementation constraints, prevention, and the responsiveness of the community. The research methods was qualitative approach. Collecting the data through in-depth interviews, documentation, and observation. Informants from SKPD that is related to the prevention of drug abusers, employee from BNN Surabaya, and a third resident of drug abusers in Surabaya had selected by purposive sampling. The results in phase to the target is not in accordance with the Perwali, because it still has obstacles ie outreach to street children, and the commitment in activities. The government's efforts in implementing prevention programs of drug abusers were in conformity with Perwali, including socialization, curriculum integration on antidrug, TOT, the establishment of peer counselor, and the establishment of the youth anti-drug cadre. Responsiveness of people have started going well. People have the awareness and courage to report drug abuse related to BNN city of Surabaya to be rehabilitated. Keywords: government suport, drug prevention, Surabaya